The Administration of Development and the Fourth Industrial Revolution: The Transformation of Management of the Life and the Nation and State - Murdiansyah Herman; M. Sayuti Enggok (Indonesian Association for Public Administration (IAPA), 2019)
The The Administration of Development traditionally consist of in one side The Development of Administration as an effort to improve State administration which includes, improvement of organization, staffing, finance and so on. On the other side, the Administration of Development itself formulated and implemented of public policies both as the process of State administration and political processes. The scope of the Administration of Development both in the development of administration and administration of development itself requires contextual transformation as dealing with the reality that there has been changes in the life situation of the nation and state. The life of the nation and state has rapidly changes both in terms of ideology, politics, economy, social, culture, defense and security even science and technology. The Impact of the Fourth Industrial Revolution as part of the changes and technological advancements of which among them related to the automation has a major impact to the paradigm shift in the management of the life of the nation and state as well to the Administration of Development